Education for sustainable development in Malaysia: a study of teacher and student awareness - Hanifah Mahat; Shaharudin Idrus (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Sustainable development is seen as a modern development idea that is most proactive and practical in addressing the issues of development demand and environmental conservation. This paper examined two variables influencing teachers’ and students’ awareness of education for sustainable development (ESD), namely, school location and school participation in the Sustainable School Environmental Award (SLAAS) Programme. Primary data were gathered from 447 students and 245 teachers of six secondary schools in urban areas and six secondary schools in rural areas which participated in the SLAAS Programme. Results of the statistical analysis revealed a difference in terms of content knowledge, attitude and behaviour between students in rural and urban areas and no difference for the teachers. This meant that the application of ESD as the outcome of SLAAS Programme between urban and rural students is different according to the ESD awareness variable, but not so for urban and rural teachers. Findings also revealed differences with respect to knowledge practice and behaviour for students and teachers according to school participation in the SLAAS where a significant relationship existed for schools that participated in the SLAAS at the national level. These findings might be useful in informing further effort to enhance ESD awareness of the school community particularly through sustainability activities.